2019
DOI: 10.18203/2394-6040.ijcmph20191048
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety disorder among medical students in a tertiary care hospital in Davangere, Karnataka

Abstract: Background: Social anxiety disorder is a common psychiatric illness characterized by fear of being observed and scrutinized by others. It can impair academic performance and can lead to serious withdrawal from society and depression. The objective of the study was to measure the proportion and study the associated factors of Social Anxiety Disorder among students of a tertiary medical college and hospital.Methods: This hospital-based, cross-sectional study was conducted among the 272 medical students of a Tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
2
4
0
1
Order By: Relevance
“…The overall prevalence of SAD in this study was 32.8%, and this finding is consistent with a similar study in the Ethiopian University of Gondar (31.2%), 21 and it is also in line with studies from universities of Iraq (28.3%), 7 Saudi Arabiya (29.8%), 18 India (30.5%) 19 and Australia (30.0%). 17 Agreement of these studies with our result can be explained by similar study population 7,[17][18][19]21 and using similar screening tool. 19,21 The prevalence of SAD in this study was higher than the study conducted in the UK (10%) 15 and Delhi, India (12.6%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The overall prevalence of SAD in this study was 32.8%, and this finding is consistent with a similar study in the Ethiopian University of Gondar (31.2%), 21 and it is also in line with studies from universities of Iraq (28.3%), 7 Saudi Arabiya (29.8%), 18 India (30.5%) 19 and Australia (30.0%). 17 Agreement of these studies with our result can be explained by similar study population 7,[17][18][19]21 and using similar screening tool. 19,21 The prevalence of SAD in this study was higher than the study conducted in the UK (10%) 15 and Delhi, India (12.6%).…”
Section: Discussionsupporting
confidence: 92%
“…17 Agreement of these studies with our result can be explained by similar study population 7,[17][18][19]21 and using similar screening tool. 19,21 The prevalence of SAD in this study was higher than the study conducted in the UK (10%) 15 and Delhi, India (12.6%). 16 This difference might be because of sociocultural differences between the UK and Ethiopia.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Studies have shown that 10% of college students in the United Kingdom suffer from SA ( Russell and Shaw, 2009 ). Further, 30% of newcomers suffered from SA in Australia ( Wilson, 2005 ), while the percentage of SA among students in medical specialties in Iraq, Kingdom of Saudi Arabia, and India was 28.3, 29.8, and 30.5%, respectively ( Ahmad et al, 2017 ; Hakami et al, 2017 ; Jarallah et al, 2017 ; Dsouza et al, 2019 ; Reta et al, 2020 ). SA has a significant negative impact on interpersonal relationships, work, and academic performance, such as increasing the risk of dropping out of school, reducing work efficiency, and affecting the quality of life ( Aderka et al, 2012 ; Jacobson et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ren and Li (2020) found that PE has a significant impact on the SA of left-behind children in rural Chinese areas. Moreover, some previously mentioned researchers from the United Kingdom, Austria, Iraq, Saudi Arabia, India, and Ethiopia conducted studies in their own countries ( Wilson, 2005 ; Russell and Shaw, 2009 ; Ahmad et al, 2017 ; Hakami et al, 2017 ; Jarallah et al, 2017 ; Dsouza et al, 2019 ; Reta et al, 2020 ). However, few studies have examined the relationship between PE, IA, and SA in a group of Chinese college students.…”
Section: Introductionmentioning
confidence: 99%